Lean and agile in small- and medium-sized enterprises: Complementary or incompatible? - Neeshal Gurahoo; Roger H. Salisbury (South African Journal of Business Management, 2018)
Background: This study explores the relationship between the implementation of lean supply chain management and the agility of manufacturing small- and medium-sized enterprises (SMEs). Although some studies have suggested that these two approaches are mutually exclusive, other research finds that they may be applied to different parts of the supply chain or may be compatible through the common elements of process integration and supply chain-wide collaboration. Objectives: Through an investigation of two companies at different stages of lean implementation, this study sought to establish which of these paradigms might be applicable in the context of South African SMEs. Method: Semi-structured interviews were conducted with managers at both companies, and the progress towards lean manufacturing was probed. Results: Company B was found to have made considerably more progress towards a lean system than Company A. Neither company had achieved just-in-time purchasing, and this was identified as a challenging aspect for SMEs. Both companies experienced stockouts and long lead times. The volatile nature of their markets indicated a need for greater agility. Company B was found to have a greater potential for speed, flexibility and response. It is proposed that this may be a direct consequence of greater progress in lean implementation. Conclusion: It was concluded that strategies to implement lean are a necessary prelude to achieving an agile enterprise. This article presents a model incorporating the lean principles that SMEs should adopt in order to achieve agility.
Keywords: 650